Legislate a red zone or criminalize trans identities? Social effects of a local norm in the city of Mar del Plata (Delito y Sociedad, 2024)
The following article proposes to describe and explain how the creation of an ordinance that seeks to regulate commercial sex in the city of Mar del Plata can be thought of, firstly, as a product of previous criminalization actions that constructed the social imaginary of trans women and transvestites as narco-transvestites. Secondly, this ordinance is a new mechanism of exclusion that revives old social practices of persecution of transfemininities by excluding them from public space. The results presented here are part of an ethnographic fieldwork that began in 2018 and ended in 2023, carrying out participant observation in commercial sex areas, in social settings of sex workers, in meetings with state agents, among others. In turn, ten non-directive interviews were conducted with different key informants: trans women and transvestites.
Keywords: trans woman; transvestites; criminalization